QARAQALPAQ MILLIY DÁSTÚRLERINIŃ BIRI “TUSAW KESIW” - Alimov, Q.T. (SCIENCE and SOCIETY, 2025)
This article will focus on one of the Karakalpak national traditions-the tradition of "Cutting bonds", the issues of the origin of this tradition, in which cases it existed, a comparison of the recent Cutting of bonds in our country with the past and present, and others will be considered.